Laundry Inklusif: Mewujudkan Kemandirian ABK melalui Pelatihan Manajemen Usaha dan Keuangan - Dewi Murtiningsih; Desiana Vidayanti; Oties T Tsarwan; Anizar Anizar; Belfa Yulita Nur Asifah (Pusat Riset dan Inovasi Nasional, 2025)
The implementation of community service activities (PKM) at the YPI Al Husna School has brought significant changes in enhancing the empowerment of students and teachers. Before the implementation, the school faced major challenges, including a lack of teacher competence in starting and managing businesses, as well as minimal understanding of cost calculations, profit and loss projections, and financial record-keeping. However, after conducting training and focus group discussions (FGD) on managing a school-based laundry business, the situation began to change. Teachers now possess basic knowledge about business management, including the preparation of standard operating procedures (SOP) and workflows, as well as the ability to fill out and present simple financial data with high accuracy. With the establishment of a well-managed laundry business unit, it is hoped that it can have a positive impact on the independence of special needs students. In terms of return on investment (ROI) and social return on investment (SROI), the implementation of this program shows promising potential, where the improvement of teachers' skills and students' independence can be measured through pre and post-test questionnaires, as well as the achievement of established targets, creating significant social value for the school community.